2008
DOI: 10.2172/926116
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Telemetry Studies of Juvenile Chinook Salmon Survival at the Lower Columbia Projects in 2006

Abstract: In 2006, the Portland District of the U.S. Army Corps of Engineers (USACE) contracted with the Pacific Northwest National Laboratory (PNNL) to conduct three studies using acoustic telemetry to estimate detection probabilities and survival of juvenile Chinook salmon at three hydropower projects on the lower Columbia River. The primary goals were to estimate detection and survival probabilities based on sampling with Juvenile Salmon Acoustic Telemetry System (JSATS) equipment, assess the feasibility of using JSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“…As in previous studies (Ploskey et al 2007b;, tag-detection data from JSATS autonomous nodes were processed in two ways as a quality-control measure, and we found no significant difference in detection and survival estimates based upon detection histories. One method involved using TagViz software, and the other involved processing data with programs written in the Statistical Analysis System (SAS) code.…”
Section: Data Processing and Validationsupporting
confidence: 62%
See 1 more Smart Citation
“…As in previous studies (Ploskey et al 2007b;, tag-detection data from JSATS autonomous nodes were processed in two ways as a quality-control measure, and we found no significant difference in detection and survival estimates based upon detection histories. One method involved using TagViz software, and the other involved processing data with programs written in the Statistical Analysis System (SAS) code.…”
Section: Data Processing and Validationsupporting
confidence: 62%
“…In 2006, a total survival evaluation looked at 100,000-cfs spill for 24 hours/day in spring and a modified BiOp spill with larger gate openings in summer. Unfortunately, the effects of spill condition were confounded by a typical decline in the survival rate of FC as summer progressed (Ploskey et al 2007b). …”
Section: Introductionmentioning
confidence: 99%
“…As in previous studies (Ploskey et al 2007b;Ploskey et al 2009, tag-detection data from JSATS autonomous nodes were processed in two ways as a quality-control measure, and we found no significant difference in detection and survival estimates based upon detection histories. One method involved using TagViz software, and the other involved processing data with programs written in the Statistical Analysis System (SAS) code.…”
Section: Data Processing and Validationsupporting
confidence: 66%
“…The flow conditions created by the BGS likely contributed to the observed passage distributions, especially when comparing passage at the dam to previous radio-telemetry and hydroacoustic studies (Ploskey 2007a). Those studies showed a strong southerly preference for passage highly skewed toward turbine units 11-12 at the peak, with the tail of the distribution extending toward unit 18.…”
Section: Passage Distributionmentioning
confidence: 79%
See 1 more Smart Citation